2019
DOI: 10.32598/jams.22.4.70
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Attention Bias Modification With Selective Serotonin Reuptake Inhibitors in Patients With Obsessive-Compulsive Disorder

Abstract: Background and Aim Obsessive-Compulsive Disorder (OCD) is the fourth most common psychiatric disorder. It consists of symptoms, including intrusive thoughts, rituals, behaviors, preoccupations, and compulsions. This study aimed to evaluate the effectiveness of attention bias modification and selective serotonin reuptake inhibitors in reducing the symptoms of OCD. Methods and Materials study population comprised patients with OCD referring to the outpatient clinic of Amir Kabir Hospital in Arak City, Iran. Of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Several studies revealed that CBMI and CBMA reduce cognitive biases in individuals with OCD. CBMA only reduces attention bias towards OCD-related stimuli, and presents no significant effect on the severity of OCD (Habedank et al, 2017;Mohsenpourian, Nokani, Jamilian, & Ghasemi, 2019;Rouel & Smith, 2018); while CBMI not only impacts interpretation bias, but also reduces OCD severity (Black & Grisham, 2016;Clerkin & Teachman, 2011;Dalir, Alipour, Zare, & Farzad, 2016). CBMI, in comparison with the main treatment of OCD, i.e.…”
mentioning
confidence: 99%
“…Several studies revealed that CBMI and CBMA reduce cognitive biases in individuals with OCD. CBMA only reduces attention bias towards OCD-related stimuli, and presents no significant effect on the severity of OCD (Habedank et al, 2017;Mohsenpourian, Nokani, Jamilian, & Ghasemi, 2019;Rouel & Smith, 2018); while CBMI not only impacts interpretation bias, but also reduces OCD severity (Black & Grisham, 2016;Clerkin & Teachman, 2011;Dalir, Alipour, Zare, & Farzad, 2016). CBMI, in comparison with the main treatment of OCD, i.e.…”
mentioning
confidence: 99%